2017
DOI: 10.3390/su9091666
|View full text |Cite
|
Sign up to set email alerts
|

Cashew as a High Agricultural Commodity in West Africa: Insights towards Sustainable Production in Guinea-Bissau

Abstract: Abstract:In Sub-Saharan Africa, the West African region has highly diverse agro-climatic conditions, which grant the potential for a remarkable agricultural production of a great diversity of crops. Since the 1980s, the production volumes of most crops have grown vigorously for both domestic and export markets. Traditional food crops-such as rice, groundnuts and sorghum-have been replaced by cash crops, namely cashew. Among the main cashew production areas, West Africa is the most recent and dynamic in the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 20 publications
3
74
0
2
Order By: Relevance
“…In this region where the main activity remains agriculture, it has been shown that cashew nuts have increased the incomes of farmers and people and, above all, improved their living standards [9,13]. As a result of the guarantee of sales income and lower input costs, more and more farmers in West Africa continue engaging in cashew nut production as a cash crop [3].…”
Section: Mapping Changing In Rural Landscapementioning
confidence: 99%
See 3 more Smart Citations
“…In this region where the main activity remains agriculture, it has been shown that cashew nuts have increased the incomes of farmers and people and, above all, improved their living standards [9,13]. As a result of the guarantee of sales income and lower input costs, more and more farmers in West Africa continue engaging in cashew nut production as a cash crop [3].…”
Section: Mapping Changing In Rural Landscapementioning
confidence: 99%
“…This has both a positive and negative impact on the environment. On the one hand, cashew nut orchards limit soil erosion, promote regrowth and increase tree density in savannah landscapes [3,[29][30][31]. On the other hand, by affecting the dynamics of the rural landscape, this culture leads to a deterioration in the quality of carbon sequestration [6].…”
Section: Impacts Of Cashew Nut Expansionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic foundations of most SSA are dominated by agriculture, which is recognized to contribute between 15 and 40% of the gross domestic product (GDP). Besides, agriculture sector provides livelihoods for over 70% of SSA's population through family farming [3,4]. The economically active population in agriculture doubled from 100 million people in 1980 to 212 million in 2013.…”
Section: Introductionmentioning
confidence: 99%